(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Stunting is a serious problem that needs to be handled both in Indonesia and globally. Approximately 151 million, or 22.2%, of toddlers in the world are currently stunted. The purpose of this study is to assess the relationship between adolescent pregnancy and stunting in toddlers aged 12-36 months in Bogor District, Indonesia. Method: A cross-sectional study design was employed, with primary data from a total sample of 500 toddlers in the District. Stunting status was assessed based on the height-for-age indicator <-2 z-score, while the categorization of adolescent pregnancies related to pregnant women age <20 years. The analysis of the relationship between adolescent pregnancies and stunting applied multivariate Cox regression analysis and the effect is expressed by the prevalence ratio (PR) with a 95% confidence interval (CI). Result: Our study shows that the prevalence of stunting in toddlers aged 12-36 months in Bogor District is 39.2%. The Cox regression test results of the relationship between adolescent pregnancy and stunting show a PR of 1.42 (95% CI: 1.01-1.98), which means that pregnant women who are still teenagers (<20 years) display a prevalence of stunted toddlers 1.4 times higher than those who are adult (?20 years), after being controlled by the “mother’s education” and “mother’s parenting pattern” variables. Conclusion: Stunting can be prevented by raising the maternal gestational age by increasing the minimum marriage age in accordance with Indonesian marriage law limitations at age of 19 years and get first time pregnant at age of 20 years.